Summer Drought Patterns in the Middle-Lower Reaches of the Yangtze River Basin and Their Connections with Atmospheric Circulation before and after 1980 - Shuping Li; Guolin Feng; Wei Hou (Advances in Meteorology)
The three summer drought patterns of the middle-lower reaches of the Yangtze River basin (MLRYRB) and their associated atmospheric circulation were investigated before and after 1980. For the whole-basin wide drought pattern during 1961–1979, the anomalous high ridge over Japan blocked the northerly flow from Siberia to southern China. Further, the western Pacific subtropical high (WPSH) was weaker than normal and shifted eastward. For the southern drought and northern flood pattern during 1961–1979, the zonal circulation was straight and an anomalous anticyclonic circulation was located over Japan. Less moisture was transported to southern China associated with the weakened WPSH. During 1980–2013, the WPSH extended westward and controlled the southern part of the MLRYRB, and an anomalous cyclonic circulation was centered over Japan. For the southern flood and northern drought pattern during 1961–1979, the meridional circulation was obvious, and the WPSH was weaker than normal. The anomalous southwesterly moisture transport appeared to southern China. However, during 1980–2013 the continental high pressure impacted northern China. The WPSH shifted eastward and the anomalous northeasterly moisture transport presented over eastern China.